1994
DOI: 10.1007/bfb0049406
|View full text |Cite
|
Sign up to set email alerts
|

A linear-time algorithm for finding a central vertex of a chordal graph

Abstract: Abstract. In a graph G = (V, E), the eccentricity e(v) of a vertex v is max{d (v,u) : u E V}. The center of a graph is the set of vertices with minimum eccentricity. A graph G is chordal if every cycle of length at least four has a chord. We present an algorithm which computes in linear time a central vertex of a chordal graph. The algorithm uses the metric properties of chordal graphs and Tarjan and Yannakalds linear-time test for graph chordality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 12 publications
2
47
0
Order By: Relevance
“…It was also shown in [11,12] that for rectilinear link distance after two FP scans, the returned distance d(v, w) is a good approximation of the diameter of P and that a cut c passing via a middle edge of any shortest (v, w)-path is close to the center of P. Then using methods of computational geometry it is possible to compute in linear time a central point of P (another linear time algorithm for this problem has been proposed in [39]). As shown in [13], this approach can be appropriately modified to compute the centers of chordal graphs in linear time O(|E|). It was also shown that diam(G) ≥ 2rad(G) − 2 holds for such graphs.…”
Section: Related Work On Diameters and Centersmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also shown in [11,12] that for rectilinear link distance after two FP scans, the returned distance d(v, w) is a good approximation of the diameter of P and that a cut c passing via a middle edge of any shortest (v, w)-path is close to the center of P. Then using methods of computational geometry it is possible to compute in linear time a central point of P (another linear time algorithm for this problem has been proposed in [39]). As shown in [13], this approach can be appropriately modified to compute the centers of chordal graphs in linear time O(|E|). It was also shown that diam(G) ≥ 2rad(G) − 2 holds for such graphs.…”
Section: Related Work On Diameters and Centersmentioning
confidence: 99%
“…In computational geometry, the diameter and center problems have been investigated for point sets in two-or high-dimensional vector spaces endowed with usual metrics [17,22,38,45] and for polygonal or polyhedral domains with the geodesic [31,41] or link metrics [19,35,44]. For graphs and networks, efficient algorithms for these problems are known for several classes of graphs [6,13,15,18,21,30]. Most of these algorithms are based on geometric properties of classes of graphs in question.…”
Section: Introductionmentioning
confidence: 99%
“…In directed graphs, depending on the application, there may be multiple definitions for "closeness": a node can be close in the sense that it has short paths to other nodes ("source"), from other nodes ("target"), or even to and then back from other nodes ("roundtrip"). That is, there are several natural definitions of both radius and diameter for directed graphs; all of them are well-studied [28,40,27,36,6,30,26,35,11,12,57,58,23,38,54,47,25,2,17] (and many others). Even estimating the diameter and radius of a network efficiently is useful in practical applications (e.g.…”
mentioning
confidence: 99%
“…Note that a ratio of 1/2 can easily be achieved by choosing an arbitrary vertex (the eccentricity of any vertex is at least one-half the diameter of the graph) and performing a BFS starting at this vertex. It follows also from the results in [1,7] (see also paper [16] which surveyed recent results related to the computation of exact and approximate distances in graphs) that the diameter problem in unweighted, undirected graphs can be solved in Õ (min{n 3 , n 7/3 }) time with an additive error of at most 2 without matrix multiplication. Here, Õ ( f ) means O( f polylog(n)).…”
Section: Introductionmentioning
confidence: 94%